A multi-phase particle shifting algorithm for SPH simulations of violent hydrodynamics with a large number of particles. Issue 2 (4th March 2017) - Mokos, Athanasios; Rogers, Benedict D.; Stansby, Peter K.
ABSTRACT: A numerical inconsistency has emerged for multi-phase smoothed particle hydrodynamics simulations when using very high resolution, made possible by graphical processing units. In violent flows unphysical voids and phase separation occur ultimately leading to numerical instability. New Fickian-based particle shifting algorithms with a selectively activated free-surface correction are developed for air–water simulations to prevent the creation of unnatural voids and maintain numerical stability through nearly uniform distributions. Using the shifting algorithm without surface correction in the air phase is recommended, with marginal improvements if the shifting algorithm is not applied in water. However, maintaining shifting in water would avoid possible void occurrence. The improvement is demonstrated using a dry-bed dam break and a sloshing tank case. A 3D case involving the impact of the water flow on an obstacle is compared with experimental data. The multi-phase SPH scheme gives closer agreement with experiment than a single-phase simulation.